2005
DOI: 10.1126/science.1105034
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Consequences of Tropical Second-Growth Forest Regeneration

Abstract: Follow this and additional works at: http://digitalcommons.uconn.edu/eeb_articles Recommended Citation Sezen, Uzay U.; Chazdon, Robin L.; and Holsinger, Kent E., "Genetic consequences of tropical second-growth forest regeneration" (2005). EEB Articles. 2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
92
3
4

Year Published

2005
2005
2012
2012

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(117 citation statements)
references
References 5 publications
(6 reference statements)
15
92
3
4
Order By: Relevance
“…Despite the large amount of gene flow from outside, a few among the 23 adults produced a disproportionate part of the natural regeneration, especially considering the large number of spruces living below treeline and the well-known recruitment limitations at treeline (Stevens and Fox, 1991;Oleksyn et al, 1998). Similar uneven reproductive success has been reported in many studies based on parentage analysis on herbaceous and tree species (Meagher and Thompson, 1987;Dow and Ashley, 1996;Aldrich and Hamrick, 1998;Schnabel et al, 1998;Sezen et al, 2005). We found that reproductive success is not related to tree size, and that tree size is weakly related with age.…”
Section: Discussionsupporting
confidence: 69%
“…Despite the large amount of gene flow from outside, a few among the 23 adults produced a disproportionate part of the natural regeneration, especially considering the large number of spruces living below treeline and the well-known recruitment limitations at treeline (Stevens and Fox, 1991;Oleksyn et al, 1998). Similar uneven reproductive success has been reported in many studies based on parentage analysis on herbaceous and tree species (Meagher and Thompson, 1987;Dow and Ashley, 1996;Aldrich and Hamrick, 1998;Schnabel et al, 1998;Sezen et al, 2005). We found that reproductive success is not related to tree size, and that tree size is weakly related with age.…”
Section: Discussionsupporting
confidence: 69%
“…the harvester's preference for individuals with greater diameter at breast height results in the removal of only a part of a population's diversity, and the rest remains in the earlier stages (seedlings and juveniles). in fact, Santos (2004) demonstrated a slight but significantly higher polymorphism in seedlings of Rosewood in comparison to the adult stage in the adolpho Ducke Forest Reserve (manaus population), supporting such a hypothesis (but see Sezen et al, 2005). moreover, high outcrossing rates (expected in Rosewood) and large effective population sizes have been invoked as factors that would maintain the genetic diversity and structure of the population even under silvicultural management (Robledoanuncio et al, 2004).…”
Section: Distribution Of the Genetic Diversity In Rosewood Populationsmentioning
confidence: 72%
“…First, gene flow may swamp local selective pressures. Seed dispersers often range widely (Holbrook & Smith 2000) and dispersal distances can reach nearly 1km in this region (Sezen et al 2005). This fact suggests that populations of plants with ranges spanning several hundred meters of elevation may exchange genes regularly, precluding adaptation to the local biotic environment.…”
Section: Discussionmentioning
confidence: 99%